Polyolefin composition for coating molding
The catalyst preparation using asymmetric hafnium metallocene of n-propylcyclopentadienyl ligand was solved by increasing density in coating molding, and a single peak polyolefin composition with high modulus, good impact strength and ESCR was achieved, reducing product specifications and maintaining processability.
Patent Information
- Application Number
- CN202380054264.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-08-04
- Publication Date
- 2025-03-04
AI Technical Summary
During the coating molding process, the increase in the density of single reactor single-peak polymers leads to a decrease in impact strength and environmental stress cracking resistance, making it difficult to simultaneously reduce product specifications and maintain performance.
A catalyst composition was prepared using asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand, and a single-modal polyolefin composition with high modulus, good impact strength and ESCR was prepared by contacting ethylene and α-olefin comonomer.
Higher modulus, greater impact strength and good ESCR are achieved, reducing the specifications of the condensation molded products while maintaining good machining.
Smart Images

Figure CN119562977A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure are directed to polyolefin compositions useful for slush molding. Background Art
[0002] The use of polyolefin compositions in forming molded articles is well known. Any conventional method may be used to produce such polyolefin compositions. Various polymerization techniques using different catalyst systems have been used to produce such polyolefin compositions suitable for forming articles. Summary of the invention
[0003] The present disclosure provides various embodiments, including but not limited to the following polyolefin composition, wherein the polyolefin composition has:
[0004] 0.925g / cm 3 Up to 0.960g / cm 3 density; a melt index (I2) of 1.0 dg / min to 10.0 dg / min; an Mn of 17,000 to 40,000; an Mw of 50,000 to 120,000; an Mz of 120,000 to 300,000;
[0005] A molecular weight distribution (Mw / Mn) of 2.0 to 3.5; and a molecular weight comonomer distribution index relative to density such that: molecular weight comonomer distribution index > -161.2*density + 152.5. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 is a plot of 1% secant modulus versus density according to embodiments of the present disclosure.
[0007] Figure 2 is a plot of molecular weight comonomer distribution index (MWCDI) versus density according to embodiments of the present disclosure.
[0008] Figure 3 is a plot of molecular weight comonomer distribution index (MWCDI) versus density according to embodiments of the present disclosure. DETAILED DESCRIPTION
[0009] Slush molding is a high temperature, zero shear process that can be used to make articles. Reducing specifications to produce lightweight products while maintaining processability and performance is desirable with slush molding. Higher density polymers, such as polyolefins, can help provide a reduction in product specifications. However, for single reactor unimodal polymers, this increase in density can result in an undesirable reduction in impact strength and / or environmental stress crack resistance (ESCR).
[0010] Slush molding compositions and slush molding methods are discussed herein. Advantageously, the present disclosure provides unimodal compositions having higher modulus, greater impact strength, and good ESCR and processability compared to other slush molding compositions. Unimodal compositions having higher modulus and good toughness and processability enable downsizing of slush molding products.
[0011] The slush molding compositions discussed herein, such as catalyst slush molding compositions, are prepared using asymmetric hafnium metallocenes having n-propylcyclopentadienyl ligands. These slush molding compositions can be used to prepare polyolefin compositions having a number of desirable properties, such as having an inverse comonomer distribution (defined as MWCDI>0) and / or an improved (i.e., higher) molecular weight comonomer distribution index (MWCDI) compared to other polyolefin compositions prepared by other metallocenes. In addition, these slush molding compositions can be used to prepare polyolefin compositions having desirable ESCR for slush molding. 50 In addition, these slush molding compositions can be used to prepare polyolefin compositions having improved (ie, lower) zero shear viscosities compared to other polyolefin compositions of similar density prepared from other metallocenes.
[0012] The asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand can be represented by structure (I):
[0013]
[0014] Where: R 1 is n-propyl, and each X is independently a leaving group. As shown in structure (I), the cyclopentadienyl ring is R 1 The cyclopentadienyl ring is not substituted. 1 The first cyclopentadienyl group is substituted and the other cyclopentadienyl ring is not substituted, in other words the two cyclopentadienyl ligands are different, so the metallocene can be called an asymmetric hafnium metallocene.
[0015] Embodiments of the present disclosure provide that X is a leaving group. One or more embodiments provide that X is selected from alkyl, aryl, hydride and halogen. One or more embodiments provide that X is selected from halogen, (C1-C5) alkyl, CH2SiMe3 and benzyl. One or more embodiments provide that X is selected from alkyl and halogen. One or more embodiments provide that X is chlorine. One or more embodiments provide that X is methyl.
[0016] Examples of X include halogen ions, hydrides, (C1 to C 12 ) alkyl, (C2 to C 12 )alkenyl, (C6 to C 12 ) aryl, (C7 to C 20) alkylaryl, (C1 to C 12 ) alkoxy, (C6 to C 16 )aryloxy, (C7 to C8)alkylaryloxy, (C1 to C 12 ) fluoroalkyl, (C6 to C 12 ) fluoroalkyl and (C1 to C 12 ) heteroatom-containing hydrocarbons and their substituted derivatives; one or more embodiments include hydrides, halides, (C1 to C6) alkyls, (C2 to C6) alkenyls, (C7 to C 18 )alkylaryl, (C1 to C6)alkoxy, (C6 to C 14 ) aryloxy, (C7 to C 16 ) alkyl aryloxy, (C1 to C6) alkyl carboxylate, (C1 to C6) fluorinated alkyl carboxylate, (C6 to C 12 ) aryl carboxylate, (C7 to C 18 )alkylaryl carboxylates, (C1 to C6)fluoroalkyl, (C2 to C6)fluoroalkenyl and (C7 to C 18 ) fluoroalkylaryl; one or more embodiments include hydride, chloride, fluoride, methyl, phenyl, phenoxy, benzoyloxy, tosyl, fluoromethyl and fluorophenyl; one or more embodiments include (C1 to C 12 ) alkyl, (C2 to C 12 )alkenyl, (C6 to C 12 ) aryl, (C7 to C 20 ) alkylaryl, substituted (C1 to C 12 ) alkyl, substituted (C6 to C 12 ) aryl, substituted (C7 to C 20 ) alkylaryl and (C1 to C 12 ) containing heteroatom alkyl, (C1 to C 12 ) containing heteroatoms and (C1 to C 12 ) containing heteroatom alkylaryl; one or more embodiments include chloride, fluoride, (C1 to C6) alkyl, (C2 to C6) alkenyl, (C7 to C 18 ) alkylaryl, halo(C1 to C6)alkyl, halo(C2 to C6)alkenyl and halo(C7 to C 18 ) alkylaryl; one or more embodiments include fluoride, methyl, ethyl, propyl, phenyl, methylphenyl, dimethylphenyl, trimethylphenyl, fluoromethyl (monofluoromethyl, difluoromethyl and trifluoromethyl) and fluorophenyl (monofluorophenyl, difluorophenyl, trifluorophenyl, tetrafluorophenyl and pentafluorophenyl).
[0017] Other non-limiting examples of X groups include amines, phosphines, ethers, carboxylates, dienes, hydrocarbon groups with 1 to 20 carbon atoms, fluorinated hydrocarbon groups (e.g., -C6F5(pentafluorophenyl)), fluorinated alkyl carboxylates (e.g., CF3C(O)O-), hydrides, halogen ions, and combinations thereof. Other examples of X ligands include alkyl groups such as cyclobutyl, cyclohexyl, methyl, heptyl, tolyl, trifluoromethyl, tetramethylene, pentamethylene, methylene, methoxy, ethoxy, propoxy, phenoxy, bis(N-methylaniline), dimethylamido, and dimethylphosphoryl, etc. In one embodiment, two or more X form a part of a fused ring or ring system. In one or more embodiments, X can be a leaving group selected from the group consisting of chloride, bromide, (C1 to C5), thiazolyl, ... 10 ) alkyl, (C2 to C 12 ) alkenyl, carboxylate, acetylacetonate, and alcoholate. In one or more embodiments, X is methyl.
[0018] The asymmetric hafnium metallocenes with n-propylcyclopentadienyl ligands discussed herein can be prepared by contacting a hafnium complex with an alkali metal complex to prepare an asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand. The asymmetric hafnium metallocenes with n-propylcyclopentadienyl ligands discussed herein can be prepared by methods for preparing known metallocenes (e.g., using conventional solvents, reaction conditions, reaction times, and isolation procedures).
[0019] Alkali metal complexes can be represented by one of the following structures:
[0020]
[0021] Where M' is lithium, sodium or potassium, and R 1 It's n-propyl.
[0022] One or more embodiments provide that the hafnium complex may be represented by one of the following structures:
[0023]
[0024] Where R 1 It's n-propyl.
[0025] One or more embodiments provide that the preparation of an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand (e.g., wherein each X is Cl) comprises contacting an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand with two molar equivalents of an organomagnesium halide of formula RMg(halide) or one molar equivalent of R2Mg, wherein R is (C1-C5)alkyl, CH2SiMe3, or benzyl; and the halide is Cl or Br, to prepare an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand of structure (I), wherein each X is a halogen, (C1-C5)alkyl, CH2SiMe3, or benzyl. One or more embodiments provide that X is (C1-C5)alkyl, CH2SiMe3, or benzyl. As used herein, all references to the Periodic Table of the Elements and its Groups refer to the NEW NOTATION as published in HAWLEY'S CONDENSED CHEMICAL DICTIONARY, Thirteenth Edition, John Wiley & Sons, Inc. (1997) (reproduced with permission from IUPAC), unless reference is made to the previous IUPAC form marked with Roman numbering (which also appears therein) or unless otherwise mentioned.
[0026] As used herein, "alkyl" includes straight chain, branched chain, and cyclic alkane radicals lacking one hydrogen. Thus, for example, CH3 ("methyl") and CH2CH3 ("ethyl") are examples of alkyl radicals.
[0027] As used herein, "alkenyl" includes straight chain, branched chain, and cyclic alkene groups lacking one hydrogen group; alkynyl includes straight chain, branched chain, and cyclic ethynyl groups lacking one hydrogen group.
[0028] As used herein, "aryl" groups include phenyl, naphthyl, pyridyl and other groups whose molecules have ring structures characteristic of benzene, naphthylene, phenanthrene, anthracene, etc. It should be understood that "aryl" groups can be C6 to C 20 Aryl groups. For example, a C6H5 aromatic structure is a "phenyl" and a C6H42 aromatic structure is a "phenylene". An "aralkyl" group is an alkyl group with a pendant aryl group. It should be understood that an "aralkyl" group can be (C7 to C 20 ) aralkyl groups. "Alkaryl" is an aryl group having one or more pendant alkyl groups.
[0029] As used herein, "alkylene" includes straight chain, branched, and cyclic hydrocarbon groups lacking two hydrogens. Thus, CH2 ("methylene") and CH2CH2 ("ethylene") are examples of alkylene groups. Other groups lacking two hydrogen groups include "arylene" and "alkenylene".
[0030] As used herein, the term "heteroatom" includes any atom selected from the group consisting of B, Al, Si, Ge, N, P, O and S. A "heteroatom-containing group" is a hydrocarbon group containing heteroatoms and may contain one or more of the same heteroatoms or different heteroatoms, and may contain 1 to 3 heteroatoms in a particular embodiment. Non-limiting examples of heteroatom-containing groups include groups (monovalent and divalent) of imines, amines, oxides, phosphines, ethers, ketones, oxazoline heterocycles, oxazolines and thioethers.
[0031] As used herein, the term "substituted" means that one or more hydrogen atoms in the parent structure have been independently replaced with a substituent atom or group.
[0032] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein can be used to prepare catalyst compositions. These compositions include the asymmetric hafnium metallocene discussed herein and an activator. The asymmetric hafnium metallocene discussed herein can be contacted with an activator to prepare a catalyst composition. One or more embodiments provide that the activator is an alkylaluminoxane, such as methylaluminoxane. As used herein, "activator" refers to any supported or unsupported compound or combination of compounds, which can, for example, activate a complex or catalyst component by generating a cationic species of a catalyst component. For example, this can include capturing at least one leaving group, such as the "X" group described herein, from the metal center of a complex / catalyst component (e.g., an asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand of structure (I)). An activator may also be referred to as a "co-catalyst". As used herein, "leaving group" refers to one or more chemical moieties that are combined with a metal atom and can be captured by an activator, thereby generating a substance that is active for olefin polymerization. Various catalyst compositions, such as olefin polymerization catalyst compositions are known in the art, and different known catalyst composition components can be used. Different amounts of the known catalyst composition components may be used in different applications.
[0033] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein can be used to prepare a spray-dried composition. As used herein, a "spray-dried composition" refers to a composition comprising a number of components that has undergone a spray-drying process. Various spray-drying methods are known in the art and are suitable for forming the spray-dried compositions disclosed herein. One or more embodiments provide for spray-dried compositions comprising an adjusted composition.
[0034] In one or more embodiments, the spray drying process may include atomizing a composition comprising an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand discussed herein. Many other known components may be used in the spray drying process. Atomizers such as atomizing nozzles or centrifugal high-speed disks may be used, for example, to produce a spray or dispersion of composition droplets. The droplets of the composition may then be rapidly dried by contact with an inert dry gas. An inert dry gas may be any gas, such as nitrogen, that is not reactive under the conditions employed during atomization. An inert dry gas may encounter the composition at the atomizer, which produces a droplet stream on a continuous basis. The dried composition particles may be captured from the process in a separator, such as a cyclone separator, which may separate the solid formed from a gas mixture of a dry gas, a solvent, and other volatile components.
[0035] For example, the spray-dried composition can have a free-flowing powder form. After the spray-drying process, the spray-dried composition and many known components can be used to form a slurry. The spray-dried composition can be used together with a diluent to form a slurry suitable for, for example, olefin polymerization. In one or more embodiments, the slurry can be merged with one or more other catalysts or other known components before being delivered in a polymerization reactor.
[0036] In one or more embodiments, the spray-dried composition can be formed by contacting spray-dried activator particles (such as spray-dried MAO) with a solution of an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand as discussed herein. Such solutions can typically be prepared in, for example, an inert hydrocarbon solvent, and are sometimes referred to as a conditioning solution. Such spray-dried compositions comprising contacting a conditioning solution of an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand with spray-dried activator particles (such as spray-dried MAO) can be prepared in situ in the feed line to a gas phase polymerization reactor by contacting the conditioning solution with a slurry of spray-dried activator particles (usually in mineral oil).
[0037] Various spray drying conditions can be used for different applications. For example, the spray drying process can utilize a drying temperature of 75° C. to 185° C. Other drying temperatures are also possible, wherein the temperature may depend on the metallocene and activator particles. Various sizes of orifices of the atomizing nozzle employed during the spray drying process can be used to obtain different particle sizes. Alternatively, for other types of atomizers such as disks, the rotation speed, disk size, and number / size of holes can be adjusted to obtain different particle sizes. One or more embodiments provide that fillers can be used in the spray drying process. Different fillers and their amounts can be used for various applications.
[0038] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein can be used to prepare polyolefin compositions, such as polymers. For example, the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand can be activated, i.e., activated with an activator, to prepare a catalyst. One or more embodiments provide that the spray-dried composition comprises an activator. As used herein, "activator" refers to any supported or unsupported compound or combination of compounds, which can activate the complex or catalyst component, such as by generating a cationic species of the catalyst component, for example, to provide a catalyst. The activator may also be referred to as a "cocatalyst". The activator may include a Lewis acid or a non-coordinating ion activator or an ionizing activator, or any other compound including a Lewis base, an alkyl aluminum and / or a conventional cocatalyst. The activator includes methylaluminoxane (MAO) and modified methylaluminoxane (MMAO), etc. One or more embodiments provide that the activator is methylaluminoxane. Activation conditions are well known in the art. Known activation conditions can be used.
[0039] The molar ratio of the metal (e.g., aluminum) in the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands can be 1500: 1 to 0.5: 1, 300: 1 to 1: 1, or 150: 1 to 1: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands is at least 75: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands is at least 100: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands is at least 150: 1.
[0040] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein and many other components can be loaded on the same or separate carriers, or one or more of these components can be used in an unloaded form. The use of the carrier can be achieved by any technology used in the art. One or more embodiments provide that a spray drying process is utilized. The carrier can be functionalized. One or more embodiments provide that the spray-dried composition comprises a carrier.
[0041] "Carrier" may also be referred to as "support", and refers to any carrier material, including porous carrier materials (such as talc), inorganic oxides and inorganic chlorides. Other carrier materials include resin carrier materials (such as polystyrene), functionalized or cross-linked organic carriers (such as polystyrene divinyl benzene polyolefins or polymeric compounds), zeolites, clays or any other organic or inorganic carrier materials, etc., or mixtures thereof.
[0042] The support material includes an inorganic oxide including a Group 2, 3, 4, 5, 13 or 14 metal oxide. Some preferred supports include silica, fumed silica, alumina, silica-alumina and mixtures thereof. Some other supports include magnesium oxide, titanium oxide, zirconium oxide, magnesium chloride, montmorillonite, phyllosilicates, zeolites, talc, clays and the like. Moreover, combinations of these support materials may be used, such as silica-chromium, silica-alumina, silica-titania and the like. One or more embodiments provide that the support is silica, and one or more embodiments provide that the support is hydrophobic fumed silica. One or more embodiments provide that the support is dehydrated silica. Additional support materials may include porous acrylic polymers, nanocomposites, aerogels, spherulites and polymer beads. An example of a support is available under the trade name Cabosil TM Fumed silica obtained from TS-610, or other TS-series or TG-series supports available from Cabot Corporation. Fumed silica is typically silica having a particle size of 7 to 30 nanometers that has been treated with dimethylsilyl dichloride such that most of the surface hydroxyl groups are capped.
[0043] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein and olefins can be contacted under polymerization conditions to prepare a polymer, such as a polyolefin composition. The polymerization process can be a solution polymerization process, a suspension polymerization process, a slurry polymerization process and / or a gas phase polymerization process. The polymerization process can utilize known equipment and reaction conditions, such as known polymerization conditions. The polymerization process is not limited to any particular type of polymerization system. The polymer can be used in many articles, such as coated molded articles.
[0044] One or more embodiments specify that the polyolefin composition utilizes a gas phase reactor system to prepare. One or more embodiments specify that, for example, contrary to utilizing a series of reactors, utilizes a single gas phase reactor. In other words, the polymerization reaction only occurs in one reactor. For example, a fluidized bed reactor can be utilized to prepare polymers. Gas phase reactors are known, and known components can be used in fluidized bed reactors.
[0045] As used herein, "olefins" which may be referred to as "alkenes" refer to linear, branched or cyclic compounds including carbon and hydrogen and having at least one double bond. As used herein, when polyolefins, polyolefin compositions, polymers and / or copolymers are referred to as comprising olefins (e.g., prepared by olefins), the olefins present in such polymers or copolymers are olefins in polymerized form. For example, when it is said that the ethylene content of the copolymer is 75% to 95% by weight, it is understood that the polymer units in the copolymer are derived from ethylene in the polymerization reaction, and based on the gross weight of the polymer, the derived units are present in 75% to 95% by weight. High-grade alpha-olefins refer to alpha-olefins with 3 or more carbon atoms.
[0046] The polyolefin prepared with the composition discussed herein can be prepared from olefin monomers, such as ethylene (i.e., polyethylene) or propylene (i.e., polypropylene), and other substances specified herein, wherein the polyolefin is a homopolymer prepared only from olefin monomers (e.g., prepared from 100% by weight ethylene or 100% by weight propylene). Alternatively, the polyolefin composition discussed herein can be prepared from olefin monomers (such as ethylene (i.e., polyethylene)) and straight or branched higher alpha-olefin monomers containing 3 to 20 carbon atoms. Examples of higher alpha-olefin monomers include, but are not limited to, propylene, butene, pentene, 1-hexene, and 1-octene. Examples of polyolefins include ethylene-based polymers with at least 50% by weight ethylene, including ethylene-1-butene, ethylene-1-hexene, and ethylene-1-octene copolymers, etc. One or more embodiments provide that, based on the total weight of the polymer, the polyolefin composition can include 50% by weight to 99.9% by weight of units derived from ethylene. The polyolefin composition of the present invention can be used to prepare the polyolefin composition of the present invention.Comprise all single values and subranges of 50 wt % to 99.9 wt %; For example, based on the gross weight of the polyolefin composition, polymkeric substance can comprise the unit derived from ethylene of 50 wt %, 60 wt %, 70 wt %, 80 wt % or 90 wt % to the upper limit of 99.9 wt %, 99.7 wt %, 99.4 wt %, 99 wt %, 96 wt %, 93 wt %, 90 wt % or 85 wt % derived from ethylene.Based on the gross weight of the polyolefin composition, the polyolefin composition can comprise the unit derived from comonomer of 0.1wt % to 50wt %.One or more embodiments specify, use ethylene as monomer and use hexene as comonomer.
[0047] As mentioned, polymers prepared with the compositions disclosed herein can be prepared in a fluidized bed reactor. The fluidized bed reactor can have a reaction temperature of 10°C to 130°C. All individual values and subranges from 10°C to 130°C are included; for example, the fluidized bed reactor can have a reaction temperature of 10°C, 20°C, 30°C, 40°C, 50°C, or 55°C to an upper limit of 130°C, 120°C, 110°C, 100°C, 90°C, 80°C, 70°C, or 60°C.
[0048] The fluidized bed reactor can have an ethylene partial pressure of 30 pounds per square inch (psi) to 250 psi, including all individual values and subranges from 30 to 250; for example, the fluidized bed reactor can have an ethylene partial pressure of 30 psi, 45 psi, 60 psi, 75 psi, 85 psi, 90 psi, or 95 psi on the lower limit and 250 psi, 240 psi, 220 psi, 200 psi, 150 psi, or 125 psi on the upper limit.
[0049] One or more embodiments provide that ethylene is used as a monomer and hexene is used as a comonomer. The fluidized bed reactor can have a comonomer to ethylene molar ratio of 0.0001 to 0.100, for example C6 / C2. All individual values and subranges from 0.0001 to 0.100 are included; for example, the fluidized bed reactor can have a comonomer to ethylene molar ratio of 0.0001, 0.0005, 0.0007, 0.001, 0.0015, 0.002, 0.007, or 0.010 to an upper limit of 0.100, 0.080, or 0.050.
[0050] When hydrogen is used in the polymerization process, the fluidized bed reactor can have, for example, a hydrogen to ethylene molar ratio (H2 / C2) of 0.00001 to 0.90000. All individual values and subranges from 0.00001 to 0.90000 are included; for example, the fluidized bed reactor can have a H2 / C2 with a lower limit of 0.00001, 0.00005, or 0.00008 to an upper limit of 0.90000, 0.500000, 0.10000, 0.01500, 0.00700, or 0.00500. One or more embodiments provide that hydrogen is not utilized.
[0051] The comonomer distribution or short chain branching distribution in ethylene / α-olefin copolymers can be characterized as normal (also known as having a Ziegler-Natta distribution), inverse (also known as having a broad orthogonal composition distribution (BOCD)), or flat. Several reported methods are used to quantify BOCD. In this article, a simple straight line fit is used so that the normal or inverse nature of the comonomer distribution can be quantified by the molecular weight comonomer distribution index (MWCDI), which is the slope of the linear regression of the comonomer distribution measured by composition GPC, where the x-axis is Log (MW) and the y-axis is the weight percentage of the comonomer. When the MW detector response is <0.1, the composition data is omitted. When MWCDI>0, the inverse comonomer distribution is defined, and when MWCDI<0, the normal comonomer distribution is defined. When MWCDI=0, the comonomer distribution is said to be flat. In addition, MWCDI quantifies the magnitude of the comonomer distribution. Comparing two polymers with MWCDI>0, the polymer with the larger MWCDI value is defined as having a larger, i.e., increased BOCD; in other words, the polymer with the larger MWCDI value has a larger reverse comonomer distribution. A polymer with a relatively larger MWCDI (i.e., BOCD) can provide one or more improved physical properties compared to a polymer with a relatively smaller MWCDI.
[0052] The polyolefin compositions disclosed herein are unimodal, for example, in contrast to bimodal. As used herein, "unimodal" refers to a polyolefin polymer characterized by having one peak (one maximum) in a GPC chromatogram showing molecular weight distribution. In addition, a unimodal composition is a composition prepared by using a single catalyst (e.g., a single polyethylene catalyst) in a single reactor. This distinguishes a unimodal composition as defined above from a bimodal composition that may have one peak in a GPC chromatogram showing molecular weight distribution. These bimodal compositions are those prepared by one or more polyethylene catalysts in a graded reactor process, which is typically a dual reactor process, including but not limited to two solution polyethylene reactors or two gas phase polymer reactors or two slurry phase polymerization reactors or a combination thereof (such as a sequential slurry phase and a gas phase reactor), so that two different polymers of different densities and optional molecular weights are prepared in different reactors. Two or more reactors may be connected in series or in parallel or a combination thereof. Compared to the independent realization of one or more polyethylene catalysts alone, these methods can provide improved MWCDI. In the case where the molecular weights of the two components of the bimodal are sufficiently similar, the polymer may be displayed with a unimodal peak in the GPC chromatogram. Since this composition requires at least two reactors and one or more polyethylene catalysts, it is defined as a bimodal composition. In addition, two or more polyethylene catalysts in a single solution, slurry or gas phase reactor can produce a bimodal polymer that may have a single peak in the GPC chromatogram showing the molecular weight distribution as described above. This is also defined as a bimodal polymer composition.
[0053] The polyolefin compositions disclosed herein can have a MWCDI of 0.10 to 10.00. Including all individual values and subranges from 0.10 to 10.00; for example, the polyolefin compositions can have a MWCDI of a lower limit of 0.10, 0.50, 1.00, 1.50, or 2.50 to an upper limit of 10.00, 9.00, 8.00, 8.50, or 8.35.
[0054] One or more embodiments provide that when the polyolefin composition disclosed herein has a viscosity of 0.925 g / cm 3 Up to 0.939g / cm 3 When the density is greater than 2.5, for example, 2.5 to 10.00.
[0055] One or more embodiments provide that when the polyolefin composition disclosed herein has a viscosity of 0.940 g / cm 3 Up to 0.945g / cm 3 When the density is greater than 1.5, for example, 1.5 to 10.00.
[0056] One or more embodiments provide that when the polyolefin composition disclosed herein has a viscosity of 0.946 g / cm 3 Up to 0.950g / cm 3 When the density is greater than 1.0, for example, 1.0 to 10.00.
[0057] One or more embodiments provide that when the polyolefin composition disclosed herein has a viscosity of 0.951 g / cm 3 Up to 0.960g / cm 3 When the density is greater than 0, the MWCDI is greater than 0, for example, 0.1 to 10.00.
[0058] One or more embodiments provide that the polyolefin compositions disclosed herein have a relationship of MWCDI to density such that: MWCDI>-161.2*density+152.5. This relationship is surprising.
[0059] One or more embodiments provide that the polyolefin compositions disclosed herein have a relationship of MWCDI to density such that: MWCDI > -161.2*density + 154. This relationship is surprising.
[0060] The polyolefin compositions disclosed herein may have a 3 Up to 0.960g / cm 3 Density. Including 0.925g / cm 3 Up to 0.960g / cm 3 All individual values and subranges of; for example, the polyolefin composition may have a lower limit of 0.925 g / cm 3 , 0.930g / cm 3 , or 0.935g / cm 3 The upper limit is 0.960g / cm 3 or 0.956 g / cm 3 Density. Density can be determined according to ASTM D792.
[0061] The polyolefin compositions disclosed herein may have an ESCR F of >20 hours, such as 21 hours to 600 hours. 50 For example, one or more embodiments provide that the polyolefin composition can have an ESCR F with a lower limit of 300 hours, 350 hours, or 400 hours to an upper limit of 600 hours, 550 hours, or 500 hours. 50 ESCR F can be determined according to ASTM D-1693, Method B, in a 10 volume % aqueous Igepal CO-630 solution. 50 .
[0062] The polyolefin compositions disclosed herein can have a zero shear viscosity (ZSV) value of 800 Pa*s to 4,000 Pa*s. All individual values and subranges of 800 Pa*s to 4,000 Pa*s are included; for example, the polyolefin compositions can have a ZSV with a lower limit of 800 Pa*s, 900 Pa*s or 1,000 Pa*s to an upper limit of 4,000 Pa*s or 3,500 Pa*s.
[0063] ZSV can be determined as follows.
[0064] To prepare, the test sample can be placed in a 9.75 inch by 10.25 inch rectangular mold sleeve with a thickness of 1.85 mm and compression molded at 190° C. and 25,000 lb for 6.5 minutes. After cooling to room temperature, the resulting sample block is processed with a 25 mm diameter die cutter to remove disc-shaped creep test samples.
[0065] Before the creep measurement, a DMS (Dynamic Mechanical Spectroscopy) frequency scan was performed using 25 mm parallel plates at frequencies ranging from 0.1 rad / sec to 100 rad / sec. The test gap separating the plates was 1.5 mm, and a strain satisfying the linear viscoelastic condition, typically 10% strain, was used. Each test was performed at 190°C under a nitrogen atmosphere and isothermal conditions. To start the DMS test, the rheometer oven was first equilibrated at the desired test temperature for at least 30 min, and then the sample was loaded into the test geometry. The sample was then equilibrated in the oven with the door closed for 5 min. The test gap was then set to 1.5 mm, which generated an axial force on the sample. Once the sample released the axial force, the oven was quickly opened, and the sample was trimmed so that there was no bulge. The DMS measurement was then started after the oven was closed again. During the test, the shear elastic modulus (G'), viscous modulus (G") and complex viscosity were measured.
[0066] Immediately after the DMS frequency sweep measurement, the creep test was started with an applied stress of 20 Pa under the same temperature and atmospheric conditions. During the test, the double logarithmic plot of creep compliance versus time was continuously monitored to achieve steady-state conditions, which was recorded by obtaining a slope between 0.97 and one in the plot; the creep test was stopped once steady-state conditions were obtained. The shear strain measured during the test was then plotted against the elapsed time to analyze the shear rate at the end of the test. The zero shear viscosity of the melt sample was then obtained by dividing the applied shear stress (20 Pa) by the aforementioned shear rate.
[0067] Finally, the melt samples were evaluated for signs of degradation, whether due to crosslinking or chain scission, by performing additional DMS frequency sweep measurements on the samples immediately after the creep test (note that the DMS tests were always performed at the same temperature and atmosphere as the creep measurements and at 10% strain). The samples were considered thermally stable when the viscosity recorded at 0.1 rad / s was within 5% of the viscosity at the same frequency measured in the initial DMS test performed prior to the creep evaluation.
[0068] All creep tests, including the associated DMS frequency sweep tests, were performed on either a DHR-3 or AR-G2 rheometer, both manufactured by TA Instruments. Data analysis was performed using TA Instruments’ TRIOS software.
[0069] The polyolefin compositions disclosed herein can have a 2% secant modulus of 70 ksi to 200 ksi. All individual values and subranges of 70 ksi to 200 ksi are included; for example, the polyolefin compositions can have a 2% secant modulus with a lower limit of 70 ksi, 80 ksi or 85 ksi to an upper limit of 200 ksi, 175 ksi or 160 ksi. The 2% secant modulus can be determined according to ASTM D790 (0.45 in / min).
[0070] The polyolefin compositions disclosed herein can have a melt index (I2) of 1.0 dg / min to 10 dg / min. I2 can be determined according to ASTM D1238 (190°C, 2.16 kg). All individual values and subranges from 1.0 dg / min to 10 dg / min are included; for example, the polyolefin compositions can have an I2 with a lower limit of 1.0 dg / min, 1.5 dg / min or 2.0 dg / min to an upper limit of 10 dg / min, 9 dg / min, or 8 dg / min.
[0071] The polyolefin compositions disclosed herein may have a melt index (MI) of 10 dg / min to 250 dg / min. 21 ). 21 It can be determined according to ASTM D1238 (190°C, 21.6 kg). All individual values and subranges from 10 dg / min to 250 dg / min are included; for example, the polyolefin composition can have an I of 10 dg / min, 15 dg / min, or 25 dg / min to an upper limit of 250 dg / min, 200 dg / min, or 175 dg / min. 21 .
[0072] The polyolefin composition disclosed herein can have a weight average molecular weight (Mw) of 50,000 g / mol to 120,000 g / mol. All individual values and subranges of 50,000 g / mol to 120,000 g / mol are included; For example, the polyolefin composition can have a lower limit of 50,000 g / mol, 55,000 g / mol or 60,000 g / mol to an upper limit of 100,000 g / mol, 110,000 g / mol or 100,000 g / mol Mw. As known in the art, Mw can be determined by gel permeation chromatography (GPC). GPC is discussed herein.
[0073] The polyolefin compositions disclosed herein can have a number average molecular weight (Mn) of 17,000 g / mol to 40,000 g / mol. All individual values and subranges of 17,000 g / mol to 40,000 g / mol are included; for example, the polyolefin compositions can have a lower limit of 17,000 g / mol, 18,500 g / mol, or 20,000 g / mol to an upper limit of 40,000 g / mol, 38,000 g / mol, or 35,000 g / mol. Mn can be determined by GPC.
[0074] The polyolefin compositions disclosed herein can have a Z-average molecular weight (Mz) of 120,000 g / mol to 300,000 g / mol. All individual values and subranges of 120,000 g / mol to 300,000 g / mol are included; For example, the polyolefin compositions can have a lower limit of 120,000 g / mol, 130,000 g / mol or 150,000 g / mol to an upper limit of 300,000 g / mol, 275,000 g / mol or 250,000 g / mol. Mz can be determined by GPC.
[0075] The polyolefin compositions disclosed herein can have a weight average molecular weight to number average molecular weight ratio (Mw / Mn) of 2.0 to 3.5. All individual values and subranges from 2.0 to 3.5 are included; for example, the polyolefin compositions can have a Mw / Mn, also referred to as a molecular weight distribution or "MWD", with a lower limit of 2.0, 2.5, 2.75, or 2.8 to an upper limit of 3.5, 3.25, or 3.0 Mw / Mn.
[0076] The composition of conventional GPC is discussed below.
[0077] The chromatographic system consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven is set to 160°C and the column chamber is set to 150°C. The columns used are 4 Agilent "Mixed A" 30cm20 micron linear mixed bed columns. The chromatographic solvent used is 1,2,4 trichlorobenzene and contains 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters and the flow rate is 1.0 ml / min.
[0078] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards ranging from 580 g / mol to 8,400,000 g / mol and arranged in 6 "cocktail" mixtures with at least ten times spacing between individual molecular weights. Standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, 0.025 g of polystyrene standards were prepared in 50 ml of solvent, and for molecular weights less than 1,000,000, 0.05 g of polystyrene standards were prepared in 50 ml of solvent. The polystyrene standards were pre-dissolved at 80°C with gentle stirring for 30 minutes, then cooled and the room temperature solution transferred to a 160°C autosampler dissolution oven to cool for 30 minutes. The polystyrene standard peak molecular weights were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
[0079] M 乙烯 =A×(M 聚苯乙烯 ) B (Equation 1)
[0080] Where M is the molecular weight, A has a value of 0.4061, and B equals 1.0. A fifth order polynomial is used to fit the calibration points of the corresponding polyethylene equivalents.
[0081] Total plate counts for the GPC column set were performed with decane, which was introduced into the blank sample via a micro pump controlled by the PolymerChar GPC-IR system. The plate count of the chromatography system should be greater than 18,000 for 4 Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns.
[0082] The samples were prepared semi-automatically using the PolymerChar Instrument Control software, where the target weight of the sample was set to 2 mg / ml, and the solvent (containing 200 ppm BHT) was added to a septum-capped vial previously sparged with nitrogen via the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for 2 hours with slow shaking.
[0083] Mn was determined based on GPC results using the internal IR5 detector (measurement channel) of a PolymerChar GPC-IR spectrometer according to Equations 2-4 using the PolymerChar GPCONE software, the baseline-subtracted IR chromatogram at each equally spaced data collection point (i), and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation:
[0084]
[0085]
[0086]
[0087] To monitor the deviation over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) was used to linearly correct the pump flow (Flow (nominal)) for each sample by: substituting the RV (RV (FM样品) ) with the decane peak within the narrow standard calibration (RV (FM校准) ) were compared. It was then assumed that any changes in the decane marker peak time were related to the flow rate (flow rate (有效) ). After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) is calculated according to Equation 5. Processing of the flow marker peak is completed by PolymerChar GPCONE software. An acceptable flow rate correction is such that the effective flow rate should be within + / - 0.5% of the nominal flow rate.
[0088] Flow rate (effective) = flow rate (nominal) × (RV (FM校准) / RV (FM样品) )
[0089] (Equation 5)
[0090] The IR5 GPC octene composition calibration is discussed below.
[0091] Calibration for IR5 detector dosing was performed using at least ten ethylene-based polymer standards (octene as comonomer) produced in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor over a single site metallocene catalyst, with narrow SCB distribution and known comonomer content (e.g., by 13 C NMR method, Qiu et al., Anal. Chem.) 2009, 81, 8585-8589) in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor by a single-site metallocene catalyst, the known monomer content is in the range of from homopolymer (0 SCB / 1000 total C) to about 40 SCB / 1000 total C, where total C = carbon in the main chain + carbon in the branch chain. Each SCB standard has a weight average molecular weight of 36,000 g / mole to 126,000 g / mole, as measured by GPC. The molecular weight distribution (Mw / Mn) of each standard is 2.0 to 2.5. The SCB standard polymer properties are shown in Table A.
[0092] Table A: Copolymer Standards
[0093] Comonomer weight % IR5 Area Ratio SCB / 1000Total C M Mw / Mn 23.1 0.2411 28.9 37,300 2.22 14.0 0.2152 17.5 36,000 2.19 0.0 0.1809 0.0 38,400 2.20 35.9 0.2708 44.9 42,200 2.18 5.4 0.1959 6.8 37,400 2.16 8.6 0.2043 10.8 36,800 2.20 39.2 0.2770 49.0 125,600 2.22 1.1 0.1810 1.4 107,000 2.09 14.3 0.2161 17.9 103,600 2.20 9.4 0.2031 11.8 103,200 2.26
[0094] The “IR5 Area Ratio” (or “IR5 Area Response”) of the “Baseline-Subtracted Area Response of the IR5 Methyl Channel Sensor” to the “Baseline-Subtracted Area Response of the IR5 Measurement Channel Sensor” was calculated for each of the “Copolymer” standards. 甲基通道面积 / IR5 测量通道面积 ”)” (including standard filters and filter wheels supplied by PolymerChar: Part No. IR5FWM01 as part of the GPC-IR instrument). A linear fit of comonomer wt% frequency versus “IR5 Area Ratio” was constructed in the form of Equation 6 below:
[0095] Comonomer weight % = A0 + [A1 × (IR5 甲基通道面积 / IR5 测量通道面积 )] (Equation 6)
[0096] Where A0 is the "Comonomer wt%" intercept at "IR5 Area Ratio" of zero, and A1 is the slope of "Comonomer wt%" relative to "IR5 Area Ratio" and represents the increase in comonomer wt% as a function of "IR5 Area Ratio". For narrow PDI and narrow SCBD standard materials, the IR5 Area Ratio is equal to the IR5 Height Ratio.
[0097] The polyolefin compositions disclosed herein may have a -40°C Charpy impact strength greater than 40 J / m. For example, the polymer may have a -40°C Charpy impact strength of 40 J / m to 100 J / m. All individual values and subranges from 40 J / m to 100 J / m are included; for example, the polyolefin composition may have a -40°C Charpy impact strength with a lower limit of 40 J / m, 42 J / m, or 44 J / m to an upper limit of 100 J / m, 85 J / m, or 75 J / m. The -40°C Charpy impact strength can be determined according to ISO 179 at -40°C.
[0098] Surprisingly, the polyolefin compositions disclosed herein can have desirable higher stiffness, as measured by 1% secant modulus, compared to other polyolefin compositions. For example, the polyolefin compositions disclosed herein have a 1% secant modulus relative to density such that: 1% secant modulus>4137.4*density-3770.
[0099] For example, due to providing reverse comonomer distribution, the polyolefin compositions disclosed herein can advantageously have improved low temperature impact strength, improved ESCR F 50 and / or improved zero shear viscosity for use in a slush molding process to prepare slush molded articles. Rotational molding (also known as slush molding) is a well-known process that can be used to produce, for example, hollow plastic articles.
[0100] The slush molding process can be carried out by loading a polymer prepared with the composition disclosed herein into a mold "shell" and then rotating the mold (usually on two axes) while heating it to a temperature above the melting point of the polymer. The molten polymer flows through the mold cavity under the action of the force caused by the rotation of the equipment. The rotation lasts for a sufficient time to allow the molten polymer to cover the surface of the mold. The mold is then cooled to solidify the polymer. The final stage of the molding cycle is to remove the part from the slush molding machine. Many known components can be used in the slush molding process. Different slush molding times can be used for various applications. Different slush molding temperatures can be used for various applications. One or more embodiments provide that the slush molding process occurs at a temperature of 110°C to 400°C.
[0101] Various aspects of the disclosure are provided as follows.
[0102] Aspect 1 provides a polyolefin composition, wherein the polyolefin composition has: 0.925 g / cm 3 Up to 0.960g / cm 3 density; a melt index (I2) of 1.0 dg / min to 10.0 dg / min; an Mn of 17,000 to 40,000; an Mw of 50,000 to 120,000; an Mz of 120,000 to 300,000;
[0103] 2.0 to 3.5 molecular weight distribution (Mw / Mn); and the relationship of molecular weight comonomer distribution index to density is such that: molecular weight comonomer distribution index>-161.2*density+152.5
[0104] Aspect 2 provides the polyolefin composition according to aspect 1, wherein the polyolefin composition has a relationship of molecular weight comonomer distribution index relative to density such that: molecular weight comonomer distribution index>-161.2*density+154.
[0105] Aspect 3 provides the polyolefin composition according to any one of aspects 1 to 2, wherein the polyolefin composition has a -40°C Charpy impact strength of greater than 40 J / m.
[0106] Aspect 4 provides a polyolefin composition according to any one of aspects 1 to 3, wherein the polyolefin composition has a relationship of 1% secant modulus to density such that: 1% secant modulus>4137.4*density-3770.
[0107] Aspect 5 provides the polyolefin composition according to any one of aspects 1 to 4, wherein when the density is 0.925 g / cm 3 Up to 0.939g / cm 3 When the molecular weight comonomer distribution index is greater than 2.5, when the density is 0.940 g / cm 3 Up to 0.945g / cm 3 When the molecular weight comonomer distribution index is greater than 1.5, when the density is 0.946 g / cm 3 Up to 0.950g / cm 3 When the molecular weight comonomer distribution index is greater than 1.0, when the density is 0.951 g / cm 3 Up to 0.960g / cm 3 When the molecular weight comonomer distribution index is greater than 0.
[0108] Aspect 6 provides a polyolefin composition according to any one of aspects 1 to 5, wherein the polyolefin composition has an environmental stress crack resistance (ESCR) F of >20 hours. 50 (ASTM D-1693, Method B, 10% Igepal).
[0109] Aspect 7 provides the polyolefin composition according to any one of aspects 1 to 6, wherein the polyolefin composition is unimodal.
[0110] Aspect 8 provides a slush molded article prepared from the polyolefin composition according to any one of aspects 1 to 7.
[0111] Aspect 9 provides a method for preparing a polyolefin composition according to any one of aspects 1 to 7, the method comprising: preparing a catalyst composition using an asymmetric hafnium metallocene; and reacting the catalyst composition with ethylene and a catalyst selected from propylene and (C4-C 20 ) and optionally a comonomer of the group consisting of α-olefins to prepare the polyolefin composition.
[0112] Aspect 10 provides a method for preparing the polyolefin composition according to any one of aspects 1 to 7, the method comprising:
[0113] Using an asymmetric hafnium metallocene to prepare a catalyst composition; and reacting the catalyst composition with ethylene and a catalyst selected from propylene and (C4-C 20 ) and optionally a comonomer of the group consisting of α-olefins to prepare the polyolefin composition.
[0114] Aspect 11 provides a method according to any one of aspects 9 or 10, wherein the asymmetric hafnium metallocene has an n-propylcyclopentadienyl ligand, and the asymmetric hafnium metallocene can be represented by structure (I):
[0115]
[0116] Where R 1 n-propyl; and each X is independently a leaving group.
[0117] Example
[0118] Hafnium complex I: (n-propylcyclopentadienyl)hafnium trichloride dimethoxyethane adduct which can be represented by the following formula:
[0119]
[0120] Synthesized as follows. (n-propylcyclopentadienyl) hafnium trichloride dimethoxyethane adduct is synthesized as follows (e.g., by adapting the procedure described in WO2016 / 168448A1 of Harlan). Bis(n-propylcyclopentadienyl) hafnium dichloride is commercially available from TCI; Bis(n-propylcyclopentadienyl) hafnium dichloride (25.1 g, 54.1 mmol) is heated to 140°C in a 100 mL round-bottom flask until melted. HfCl4 (17.5 g, 54.6 mmol) in the form of a solid powder is added to the flask. The contents in the flask are heated at 140°C for approximately 30 minutes and a brown viscous liquid is formed. The 100 mL round-bottom flask is attached to a short-path distillation apparatus consisting of a glass tube (90° bend) attached to a Schlenk flask. Vacuum is drawn through the stopcock of the Schlenk flask. Distillation was performed from 105°C to 110°C under 0.4 torr vacuum. In about one hour, it was observed that most of the material distilled / sublimed into the Schlenk flask or remained in the glass tube. The solid material in the U-tube was scraped out and combined with the material in the Schlenk flask. Toluene (50 mL) and dimethoxyethane (50 mL) were added to the solid. It was heated to reflux to form a solution, and toluene (50 mL) was added. Colorless needles were formed after cooling. Pentane (200 mL) was added to further form a solid precipitate. The solid was separated by filtration, and the solid was washed with pentane (2×50 mL) and dried under vacuum to provide (n-propylcyclopentadienyl)hafnium trichloride dimethoxyethane adduct (42.2 g); the combined supernatant and washings were cooled to obtain an additional 2.6 g of product, which was isolated.
[0121] An asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand, which can be represented by the following structure (II):
[0122]
[0123] is synthesized as follows. For the above formula, as mentioned above, R 1is (n-propyl). In a glove box, (n-propylcyclopentadienyl)hafnium trichloride dimethoxyethane adduct (0.75 g, 1.56 mmol) was added to a container (oven dried 4 oz. glass jar); a Teflon coated stirring bar and 40 mL of dry toluene (40 mL) were added to the container and the contents were stirred. The contents were observed to be gray and turbid. Cyclopentadienyl lithium (1 molar equivalent) was slowly added to the container; then, the contents of the container were stirred at about 20°C for about 12 hours. Nuclear magnetic resonance (NMR) spectroscopy indicated the formation of Example 1-1 as well as some unreacted starting material. The contents of the container were further stirred at about 20°C for about 120 hours. Then, the contents of the container were filtered and the volatiles were removed under reduced pressure. The solid was recrystallized from warm hexanes and toluene; the resulting solid (Example 1-1) was isolated (total yield after recrystallization was 63.9%). 1 H and 13 C NMR spectroscopy confirmed structure (II). 1 H NMR (400 MHz, benzene-d6) δ 5.86 (s, 3H), 5.77–5.72 (m, 2H), 5.57 (t, J=2.7 Hz, 2H), 2.63–2.54 (m, 2H), 1.48–1.35 (m, 2H), 0.80 (t, J=7.3 Hz, 3H). 13 C NMR (101 MHz, benzene-d6) δ 132.81, 115.78, 114.13, 110.86, 32.38, 24.34, 14.00.
[0124] A spray-dried composition utilizing an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand represented by structure (II) was prepared as follows. A hydrophobic fumed silica (CABOSIL TS-610; 2.38 pounds) and a 10% by weight solution of methylaluminoxane (MAO) in toluene (37.0 pounds) were added to a container (13 gallon can) while mixing. Then, an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand (80 grams) and toluene (20 pounds) were added to the contents of the container while mixing. The contents of the container were then spray dried (inlet temperature 146°C; 84°C outlet temperature; 14 lbs / hr slurry inlet feed, 20,000 rpm atomizer speed) to provide a spray-dried composition (4.1 pounds).
[0125] Example 1 (polyolefin composition) was prepared using a spray-dried composition using an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand represented by the following structure (II). The polymerization used a pilot fluidized bed gas phase polymerization reactor, which includes a reactor vessel containing a fluidized bed of ethylene / α-olefin copolymer powder, and a distributor plate disposed above the bottom head, and a bottom gas inlet defined at the top of the reactor vessel and having an expansion section or a cyclone system to reduce resin fines that may escape from the fluidized bed. The expansion section defines a gas outlet. The reactor further includes a compression blower for passing a continuous circulating gas from an outlet in the expansion section at the top of the reactor vessel downwardly through a circulation loop into and into the bottom gas inlet of the reactor, and flowing through the distributor plate and the fluidized bed. The reactor also includes a cooling system that removes polymerization heat and maintains the fluidized bed at a target temperature. The composition of the gas (such as ethylene, alpha-olefins and hydrogen) is fed into the reactor and monitored by an online gas chromatograph in a circulation loop to maintain a specific concentration for controlling polymer properties. The spray-dried catalyst is fed into the reactor from a high pressure device in the form of a slurry or a dry powder, wherein the slurry is fed via a syringe pump and the dry powder is fed via a metering disk. The catalyst enters the fluidized bed below 1 / 3 of the height of the fluidized bed. The polymerization system weighs the fluidized bed and includes an isolation port that discharges the polymer product from the reactor vessel in response to the increase in the weight of the fluidized bed as the polymerization reaction proceeds. The polymerization conditions are reported in Table 1.
[0126] Example 2 was prepared as Example 1 with the changes shown in Table 1.
[0127] Various polymers were used as comparative examples: Comparative Example A (a unimodal polymer obtained from UNIVATION TECHNOLOGIES, prepared with UCAT-J catalyst, with a density of 0.935 g / cm3 and a melt index (I2) of 6.1 dg / min); Comparative Example B (a unimodal polymer obtained from UNIVATION TECHNOLOGIES, prepared with UCAT-J catalyst, with a density of 0.935 g / cm3 and a melt index (I2) of 5.5 dg / min); Comparative Example C (a commercial metallocene grade Lumicene M3581UV from TOTAL Metallocene); Comparative Example D (an experimental polymer prepared with XCAT VP 100 catalyst, with a density of 0.935 g / cm3 and a melt index (I2) of 7.2 dg / min); Comparative Example E (a commercial polymer from Dow, with a density of 0.941 g / cm3 and a melt index (I2) of 2.0 dg / min); Comparative Example F (a commercial polymer Exxon HD 8660, density is 0.943g / cm3, melt index (I2) is 2.1dg / min); Comparative Example G (commercially available polymer Nova Surpass 245, density is 0.946g / cm3, melt index (I2) is 1.8dg / min); Comparative Example H (experimental polymer from Dow, density is 0.946g / cm3, melt index (I2) is 2.0dg / min).
[0128] A number of properties were determined for the polymers. The results are reported in Tables 2-3. Melt index (I2) was determined according to ASTM D1238 (190°C, 2.16 kg), melt index (I5) was determined according to ASTM D1238 (190°C, 5 kg), melt index (I 21 ) is determined according to ASTM D1238 (190°C, 21.6 kg). Mw, Mn, Mz and Mw / Mn are determined by GPC; the molecular weight comonomer distribution index (MWCDI) is determined as discussed herein. ESCR F 50 Determined according to ASTM D-1693, Method A and Method B, in a 10 volume % aqueous Igepal CO-630 solution. Charpy impact strength is determined according to ISO 179 at -40°C. Flexural modulus, 1% secant modulus, and 2% secant modulus are determined according to ASTM D790 (0.45 in / min) and reported in kilopounds per square inch (KSI). Heat distortion temperature is determined according to ASTM D648. Zero shear viscosity (ZSV) of the polymer is obtained as described herein.
[0129] Table 1
[0130]
[0131] Table 2
[0132]
[0133]
[0134] Table 3
[0135]
[0136]
[0137] The data in Table 2 show that the polyolefin compositions of Examples 1 and 2, both of which were prepared using spray-dried compositions utilizing an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand represented by structure (II), have a molecular weight comonomer distribution index (MWCDI) greater than 0.
[0138] The data in Table 2 show that the polyolefin compositions Example 1 and Example 2 each have a molecular weight of 0.925 g / cm 3 Up to 0.955g / cm 3 density.
[0139] The data in Table 2 show that polyolefin compositions Example 1 and Example 2 each have an I2 of 1.0 dg / min to 10.0 dg / min.
[0140] The data in Table 2 show that polyolefin compositions Example 1 and Example 2 each have a Mw / Mn of 2.0 to 3.5.
[0141] The data in Table 2 show that the polyolefin compositions Example 1 and Example 2 each have a -40°C Charpy impact strength greater than 40 J / m.
[0142] Figure 1 is a plot of 1% secant modulus versus density according to embodiments of the present disclosure. Figure 1 The data show that polyolefin compositions Example 1 and Example 2 each have a relationship of 1% secant modulus to density such that: 1% secant modulus > 4137.4*density - 3770. This relationship is surprising and is not seen in the comparative examples.
[0143] Figure 2 is a plot of molecular weight comonomer distribution index (MWCDI) versus density according to embodiments of the present disclosure. Figure 2The data show that polyolefin compositions Example 1 and Example 2 each have a relationship of MWCDI to density such that: MWCDI>-161.2*density+152.5. This relationship is surprising and is not seen in the unimodal comparative examples.
[0144] Figure 3 is a plot of molecular weight comonomer distribution index (MWCDI) versus density according to embodiments of the present disclosure. Figure 2 The data show that polyolefin compositions Example 1 and Example 2 each have a relationship of MWCDI to density such that: MWCDI>-161.2*density+154. This relationship is surprising and is not seen in the unimodal comparative examples.
Claims
1. A polyolefin composition, wherein the polyolefin composition has: 0.925g / cm 3 Up to 0.960g / cm 3 density; Melt index (I2) of 1.0 dg / min to 10.0 dg / min; Mn 17,000 to 40,000; Mw 50,000 to 120,000; Mz 120,000 to 300,000; A molecular weight distribution (Mw / Mn) of 2.0 to 3.5; and The relationship of the molecular weight comonomer distribution index to the density is such that: molecular weight comonomer distribution index > -161.2*density + 152.
5.
2. The polyolefin composition of claim 1, wherein the polyolefin composition has a molecular weight comonomer distribution index relative to density such that: molecular weight comonomer distribution index>-161.2*density+154.
3. The polyolefin composition according to any one of claims 1 to 2, wherein the polyolefin composition has a -40°C Charpy impact strength of greater than 40 J / m.
4. The polyolefin composition according to any one of claims 1 to 3, wherein the polyolefin composition has a relationship of 1% secant modulus to density such that: 1% secant modulus>4137.4*density-3770.
5. The polyolefin composition according to any one of claims 1 to 4, wherein when the density is 0.925 g / cm 3 Up to 0.939g / cm 3 When the molecular weight comonomer distribution index is greater than 2.5, when the density is 0.940 g / cm 3 Up to 0.945g / cm 3 When the molecular weight comonomer distribution index is greater than 1.5, when the density is 0.946 g / cm 3 Up to 0.950g / cm 3 When the molecular weight comonomer distribution index is greater than 1.0, and when the density is 0.951 g / cm 3 Up to 0.960g / cm 3 When the molecular weight comonomer distribution index is greater than 0.
6. The polyolefin composition according to any one of claims 1 to 5, wherein the polyolefin composition has an environmental stress crack resistance (ESCR) F of >20 hours. 50 (ASTM D-1693, Method B, 10% Igepal).
7. The polyolefin composition according to any one of claims 1 to 6, wherein the polyolefin composition is unimodal.
8. A slush-molded article prepared from the polyolefin composition according to any one of claims 1 to 7.
9. A method for preparing a polyolefin composition according to any one of claims 1 to 7, comprising: Preparation of catalyst compositions using asymmetric hafnium metallocenes; as well as The catalyst composition is reacted with ethylene and a catalyst selected from propylene and (C4-C 20 ) and optionally a comonomer of the group consisting of α-olefins to prepare the polyolefin composition.
10. A method for preparing a polyolefin composition according to any one of claims 1 to 7, comprising: Preparation of catalyst compositions using asymmetric hafnium metallocenes; and reacting the catalyst composition with ethylene and a catalyst selected from propylene and (C4-C 20 ) and optionally a comonomer of the group consisting of α-olefins to prepare the polyolefin composition.
11. The method according to any one of claims 9 or 10, wherein the asymmetric hafnium metallocene has an n-propylcyclopentadienyl ligand and the asymmetric hafnium metallocene can be represented by structure (I): Where R 1 is n-propyl; and each X is independently a leaving group.
Citation Information
Patent Citations
Method for synthesis of monocyclopentadienyl complexes of zirconium and hafnium
WO2016168448A1